PENGARUH TINGKAT PEMUPUKAN DAN HARGA JUAL TANDAN BUAH SEGAR (TBS) TERHADAP PRODUKSI DAN PENDAPATAN USAHA TANI KELAPA SAWIT RAKYAT KABUPATEN LABUHANBATU - Yudi Triyanto (UNIVERSITAS LABUHANBATU, 2019)
The research aimed to know about the level of fertility and sold price of TBC to the productivity and income of farmer effort palm field in Labuhanbatu regency. The research was done in Labuhanbatu regerency taking of sample by used stratified random sampling as many as 30 estate with extensive gardens ranging from 0,5 ha up to 10 ha and the age of its vegetation varies, i.e.ranging from 2,5 years to 18 years. Data was analized by multiple regression test, F-test and t-test againts the influence of the independent variable agains. The results showed that simultaneouly fertilizer urea, SP-36, mop and kiserit real effect againts oil palm productivity. Partially, fertilizer urea, mop and kiserit real effect againts the production of palm oil, but fertilizer sp-36 effect is not real agains oil palm productivity, the selling price of oil palsm TBS connecting unreal with in come of farmer oil palm. Keywords : Fertilization, Production and Income, Selling price of TBS